Relevance of the plasminogen activation system in the pathogenesis and progression of gastric cancer - Alpízar Alpízar, Warner (2018)
Gastric cancer is ranked as the third death-causing cancer and one of the most incident malignancies worldwide. Although Helicobacter pylori is the most well-established risk factor for the development of this neoplasm, most of the infected individuals do not develop gastric cancer. Two of the main challenges faced by the world’s scientific community in the combat against gastric cancer are the unraveling of its pathogenesis and the identification of novel ways to bring down the mortality. Malignant cell invasion of the non-neoplastic adjacent tissue and metastasis are pivotal events during cancer development and progression. Both processes are facilitated by proteases capable of degrading components of the extracellular matrix, some of which have been associated to clinico-pathological aspects of the disease. Recent studies have suggested the possible connection between H. pylori and the expression of some of these proteases in gastric mucosa. This review summarizes the current knowledge about epidemiological, clinical and biological aspects of gastric cancer; it also discusses the main findings about the involvement of the plasminogen activation system in the development and progression of this disease, as well as its potential repercussions in the clinical setting.